Configuration interaction in delta-doped heterostructures - Rozhansky, I.V.; Averkiev, N.S.; Lähderanta, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We analyze the tunnel coupling between an impurity state located in a δ-layer and the 2D delocalized states in the quantum well (QW) located at a few nanometers from the δ-layer. The problem is formulated in terms of Anderson–Fano model as configuration interaction between the carrier bound state at the impurity and the continuum of delocalized states in the QW. An effect of this interaction on the interband optical transitions in the QW is analyzed. The results are discussed regarding the series of experiments on the GaAs structures with a δ-Mn layer.